Temporary Veno-Venous ECMO for Acute Respiratory Illness in Pediatric Berlin Heart Patient. Issue 4 (July 2022) - Townsend, Madeleine L.; Sadat-Hossieny, Sara; Latifi, Samir Q.; Boyle, Gerard; Phillips, Alistair
We report the unique case of a 2-year-old male with severe heart failure requiring mechanical circulatory support with a left ventricular assist device, who developed adenovirus pneumonitis infection requiring veno-venous extracorporeal membrane oxygenation (ECMO) support. He progressed to acute respiratory failure and refractory hypoxemia despite intubation with maximum respiratory support. The patient was placed on ECMO with improvement in lung function over four days with subsequent successful decannulation. During the ECMO run, anticoagulation required escalation given the increased circuit surface area. Patient has since recovered and undergone heart transplantation.